Three Variants Affecting Exon 1 of Ectodysplasin A Cause X-Linked Hypohidrotic Ectodermal Dysplasia: Clinical and Molecular Characteristics - Wang, Yupei; Zhang, Chuan; Zhou, Bingbo; Hui, Ling; Zheng, Lei; Chen, Xue; Wang, Shifan; Yang, Lan; Hao, Shengju; Zhang, Qinghua (Frontiers in Genetics, 2022)
Background: Ectodysplasin A (EDA) variations are major pathogenic factors for hypohidrotic ectodermal dysplasia (HED), the most common form of ectodermal dysplasia (ED), characterized by hypotrichosis, hypohidrosis, hypodontia, and other oral features. Methods: Molecular genetic defects in three HED families were detected by whole-exome sequencing and confirmed by Sanger sequencing or multiplex ligation-dependent probe amplification. The effect of splicing variant was further verified by EDA minigene in vitro analysis. De novo deletion was confirmed by chromosomal microarray analysis. Results: Three variants (c.396 + 1 G > C, c.171-173 del GTT, and exon 1 deletion) were identified, all affecting exon 1 of the EDA gene. Variants c.396 + 1 G > C and c.171-173 del GTT were first identified. Minigene analysis of the splicing variant (c.396 + 1 G > C) displayed a prolonged EDA-A1 transcript containing extra 699 bp at the start of intron 1, representing a functional cryptic splice site formation in vitro. Combining the results of chromosomal microarray analysis and whole-exome sequencing, the deletion variant was over 87 kb. Three variants were predicted to affect protein function to differing degrees, and were responsible for X-linked HED with varying phenotype. Conclusion: Investigating the clinical and molecular characteristics of these variations broadens our understanding of EDA gene variants, supporting clinical diagnosis, genetic counseling, and prenatal diagnosis of HED.